PHRASEOLOGICAL REPRESENTATION OF THE ELEMENT “FIRE” IN ENGLISH AND UZBEK LINGUISTIC CULTURES - Turgunova Shakhnoza Tursunbayevna (International Journal of Literature and Language Studies, 2026)
This article analyzes the “fire” concept in English and Uzbek linguistic cultures through phraseological units. In the course of the research, the semantic, symbolic, and cultural aspects of the “fire” element are revealed, and its role in human psychology, social relations, and national mentality is scientifically substantiated. Additionally, the broad scope of the concept is demonstrated with the help of supplementary phraseological units.